Salvage of Venous Congestion in a Reverse Anterolateral Thigh Flap Using Leech Therapy: A Case Report - Mulyadi Mulyadi; Fakhrul Hendra; Ozi Rahmat Firdaus; Anisa Sarah Utami (Fakultas Kedokteran Universitas Riau, 2026)
Venous congestion remains one of the most serious complications following reverse anterolateral thigh (ALT) flap reconstruction. If left untreated, it may result in irreversible microvascular damage and flap failure. This case demonstrates the effective use of medicinal leech therapy as a non-surgical salvage method for venous congestion in a reverse ALT flap. A 25-year-old man presented with an open proximal tibial fracture and a 9 × 7 cm anterior knee defect following a traffic accident. Reconstruction was performed using a reverse ALT flap. On the fifth postoperative day, the flap showed signs of venous congestion, and leech therapy was initiated with four leeches applied daily to the congested areas for seven days. The flap showed gradual improvement in color, temperature, and perfusion. A transient drop in hemoglobin (8.1 g/dL) required blood transfusion, but no infection or flap necrosis occurred. Leech therapy promotes venous drainage and improves microcirculation through anticoagulant and vasodilatory effects. Despite potential risks of anemia and infection, it remains a safe and practical salvage technique when surgical revision is not feasible. Medicinal leech therapy represents a simple, effective, and accessible option for managing venous congestion after reverse ALT flap reconstruction, particularly in resource-limited settings where advanced monitoring and microsurgical revision are not available.